A novel thermooptic polymer switch based on directional coupler structure - Khamis, Azme; Ismail, Zuhaimy; Haron, Khalid; Mohammed, Ahmad Tarmizi (Science Publications, 2005)

(untitled)
A novel thermooptic (TO) polymer switch based on directional coupler structure is proposed for the first time. The key element of the proposed switch is a buried square core polymer waveguides which has been designed for optimum mode matching and coupling with the single mode optical fiber configuration and have large effective index difference by the thermooptic effects. At a wavelength of 1.55 mm with the index contrast of 0.005 between the core and the cladding, the crosstalk of -40 dB and -37 dB for the cross-state and the bar-state of TO switch is demonstrated, respectively